Analisis kualitas pelayanan bartender/bartendres dalam meningkatkan kepuasan wisatawan pada sea fire salt bar di anantara uluwatu resort & spa bali - Azwar Z; Agus Muriawan Putra; Putu Ratih Pertiwi (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2020)
This research is motivated by the quality of service bartenders / bartendres who must provide good service to tourists by providing good service. The purpose of this study was to find out about the quality of bartender / bartendres services and tourist satisfaction criteria for bartender / bartendres services at the Sea Fire Salt Bar at Anantara Uluwatu Resort & Spa Bali. Data collection techniques in this study used the method of observation, interviews, questionnaires and literature studies. Data were analyzed with Quantitative Descriptive Analysis, Likert Scale and Importance - Performance Analysis The results of the study of 100 tourists from performance appraisal that affected the level of tourist satisfaction with the service quality of bartenders / bartendres at Sea Fire Salt in Anantara Uluwatu Resort & Spa Bali obtained an assessment of service quality performance categorized as good for tourist satisfaction. Of the five (5) indicators, all indicators get the same score that is said to be good, and no one answers very well. While the assessment of interests that affect the level of tourist satisfaction with the service quality of bartenders / bartendres at Sea Fire Salt in Anantara Uluwatu Resort & Spa Bali obtained an assessment of service quality performance categorized as important and very important to tourist satisfaction.Suggestions that can be given to the quality of service of the bartender / bartendres must continue to be improved so that tourists who visit get satisfaction and visitors are expected to return to visit the Sea Fire Salt Bar at Anantara Uluwatu Resort & Spa Bali